Avaliação do potencial biotecnológico da farinha de casca de mandioca na obtenção de acetato de etila com microrganismo Ceratocystis fimbriata - Araújo, Kyzzes Barreto (2016)
One of the promising ways for the residues utilization is through the development of biotechnological processes for the production of a large number of metabolites of industrial interest, such as the production of bioaromas. The fungus Ceratocystis fimbriata has the potential to synthesis of esters producing varieties of flavor compounds such as ethyl acetate, responsible for a diversity of fruit flavors. The objective this work was utilize and evaluate the biotechnological potential of cassava rind, one of the agro-industrial waste more produced in the Sergipe state, for the production of ethyl acetate through the solid state fermentation. All procedure performed obeyed an experimental design of eleven experiments corresponding to an experimental design 22 trials plus 4 axial points and three repetitions at the central point, with the variable sample mass and moisture content. The volatile compound ethyl acetate was quantified by headspace analysis on a gas chromatograph and it was found that the best experiment for the production of ethyl acetate was (91,92 μmol.L-1) with 50% humidity and 14:23 g weight dried for 48 hours fermentation. As of the best result was done other fermentation for separating the aroma using NaCl at a concentration of 5%, 10%, 15%, 20%, 25%, 30% and 35%. It was observed that NaCl concentration of 30% obtained best value (3303,60 μmol.L-1). This result has been done an increased scale to verify the influence of producing the compound ethyl acetate in a larger surface area where the experiments were performed in 1000 ml Erlenmeyer flask (10%, 20%, 30 % of the quantity of inoculum) and 2000 ml Erlenmeyer flask (50% of the quantity of inoculum). Chromatographic analysis found that 30% of saline best recovered the ethyl acetate in a 1000 ml Erlenmeyer flask with 30% inoculum (19,38 μmol.L-1).